Mechanical Modification of Nanomaterials on Fully Saturated Concrete in Groundwater Reservoir Under Long-Term Water Immersion - Hao, XianJie; Wei, Yingnan; Chen, Zeyu; Zhang, Honglan; Niu, Yifan; Chen, Kai; Huang, Ruilai (Frontiers in Materials, 2021)
With the increasing number of hydraulic structures in service, many scholars have investigated the performance of saturated concrete, however, there are few studies on the influences of different contents and types of nanomaterials on the performance of fully saturated concrete. In this paper, a series of saturated concrete experiments with different types and contents of nanomaterials are conducted, and the microstructure, mechanical properties of samples are compared and analysed. The results show that: (1) By the addition of various kinds of nanomaterials to saturated concrete, the microstructure of saturated concrete is significantly improved, and the compactness and integrity of the slurry are improved (2) The mechanical properties of saturated concrete are significantly improved by the addition of 3 wt% nanomaterials. And the compressive strength of the saturated concrete sample containing 3 wt% nano-Al2O3 is the largest and the deformation modulus of the saturated concrete sample containing 6 wt% nano-Al2O3 is the largest. (3) Compared with dry concrete, when the concrete is saturated, the modifying effect of nanomaterials on the mechanical properties of concrete is weakened. The results of this study have important guiding significance for the study of the nano-modification of hydraulic structures.